The December 2019 UK General Election: Reflections - Philip Rycroft (Revue Française de Civilisation Britannique)
The outcome of the UK General Election of December 2019 was a substantial victory for the Conservative party. Why did the Conservatives win, and win so well, when the party had been bitterly riven for over three years by deep disagreement about Brexit? This chapter analyses the reasons for that success and asks what this says about the politically unity of the United Kingdom. It argues that, beneath the surface of a decisive electoral outcome, the UK remains a country divided, demographically, socially and geographically. The future course of British politics remains uncertain.